Updated peer review of the pesticide risk assessment of the active substance asulam (variant evaluated asulam‐sodium) - European Food Safety Authority (EFSA) (Wiley, 2021)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State, the United Kingdom (France after Brexit), for the pesticide active substance asulam and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative use of asulam (variant evaluated asulam‐sodium) as a herbicide on spinach and tulip, hyacinth and lily for bulb production. MRLs were assessed in spinach. The conclusions were updated with regard to the endocrine‐disrupting properties following a mandate received from the European Commission in February 2019. In addition, the peer review also provided considerations on whether exposure to humans and the environment from the representative uses of asulam‐sodium can be considered negligible, taking into account the European Commission's draft guidance on this topic. The reliable endpoints, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified. An evaluation of data concerning the necessity of asulam‐sodium as a herbicide to control a serious danger to plant health which cannot be contained by other available means, including non‐chemical methods is also presented.